PARALLEL TECHNOLOGIES IN SOME PROBLEMS OF NETWORK MODELING - Hovhannisyan, M.H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
The paper is devoted to the analysis and programmatic implementation of directed evolution processes in complex networks. We describe the evolution model and present requirements for implementation. Then we display the developed system in architectural form and present the performance evaluation.